Biologia populacional e reprodutiva e padrão de ocupação de conchas de gastrópodos por Clibanarius antillensis Stimpson, 1859 (Crustacea: Decapoda: Diogenidae) na praia de Baixa Grande (Areia Branca/RN) - Moura, Nayara Gurgel de (2016)
The purpose of this study was providing population biology and reproduction data and to determine the shell utilization pattern of Clibanarius antillensis at Baixa Grande Beach, State of Rio Grande do Norte, Brazil (4°57’22”S / 37°08’13”W), using the percentage of the different shell type that were occupied and the morphometric relationship between hermit crabs and occupied shells. Specimens were collected at two-months intervals from October 2012 to August 2013, using sampling effort of two collectors for 1 hour during spring low tides. The hermit crabs collected were identified and had their carapace shield length measured (mm). All occupied gastropod shells were identified and had their shell biometric parameters (aperture width, aperture length and internal volume) measured (mm). A total of 576 individuals ofClibanarius antillensis was obtained of which 191 were males (33.16%), 140 nonovigerous females (24.31%), 125 intersex (21.70%) and 120 ovigerous females (20.83%), using seven species of gastropods. Cerithium atratum and Stramonita haemastoma were the most occupied shells, with 69.97%, and 24.31%, respectively. The average size of male ranged from 1.43 to 9.64 mm of CEC (4.29 ± 1.56 mm); 1.6 to 6.88 mm for non ovigerous females (3.79 ± 1.18 mm); 1.42 to 8.38 mm for intersex (3.69 ± 1.36 mm) and 2.1 to 7.27 mm for ovigerous females (3.76 ± 1.09 mm). Sexual dimorphism was recorded by the larger average size attained by males in relation to females (ovigerous and non-ovigerous) and intersexes. The shells of C. atratum had higher frequency of occupation by smaller organisms, especially in the size class 3.00 -] 4.00mm, while Stramonita haemastoma housed larger organisms, predominantly in the size class 4,00--] 5.00mm. There were differences in the pattern of occupation by males, not ovigerous females, intersex and ovigerous females. Males were significantly higher than the other categories. The size difference strongly influenced the shell utilization pattern, principaly in S. haemastoma, which has the largest Shell volume, being preffered by males. The other categories have occupied most significantly shells of C. atratum due to small size and lower width of the apperture width and length of the shells. Annual size-frequency distirbutions were unimodal, with non-normal distribution. The overall sex ratio was 1: 1.36 (M: F) and did not differ significantly from the expected sex ratio of 1: 1. Ovigerous females were present in all year-round. The fecundity of the studied population was of 178.14, with an average number of eggs of 178.14 ± 85.61 ranging from 51 eggs (CEC = 3.21 xvi mm) to 325 eggs (CEC = 6.77 mm), being much smaller than that of subtropical popultions of this species. The regression analysis shows that the number of eggs increase linearly with the increase of crabs shield lenght and internal volume of shells. Regression analysis showed a positive correlation between the dimensions of hermit crabs and the utilized shells. In this study, occupation by C. antillensis varied as a function of shell morphometric charactistic, with intraspecific differences in occupation partterns also occuring at Baixa Grande Beach